Understanding Environmental Audit in the Public Sector: Malaysian Perspective (Sains Humanika, 2013)
Environmental audit is considered a new approach and still in the evolving process. This situation has significant influence on the efforts to provide a single interpretation to be accepted by the public. Most of the definitions offered by organizations normally influenced by the nature of the organizations' operations and in general the private practices play a leading role in providing the definitions compared to the public sector. In the context of environmental audit in the public sector, definition about the audit is referred to the framework provided by the INTOSAI as the main reference to the auditors. Due to its various definitions, this study is conducted to look at how this perspective influences understanding of the public sector auditors in particular in the developing countries as the case of Malaysia. This study employed qualitative approach where interviews were conducted with selected auditors to gain their understanding about environmental audit. The result showed consistent understanding by the auditors with the established framework for environmental auditing in the public sector. Even though there were some gaps between respondents' opinion and the framework, but the framework eventually served as a fundamental for the auditors to understand about environmental audit.
Keywords: Public sector auditing; environmental audit; sustainable development